2017
DOI: 10.1007/s00011-017-1092-9
|View full text |Cite|
|
Sign up to set email alerts
|

Ouabain attenuates ovalbumin-induced airway inflammation

Abstract: Therefore, our data demonstrate that ouabain negatively modulates allergic airway inflammation induced by OVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
3
15
1
Order By: Relevance
“…It is noteworthy that in this study the authors used high doses of ouabain both in vitro and in vivo . This contrasts with other studies that show a reduction of a different pattern of cytokines, including IL-1β (Leite et al, 2015 ) with lower ouabain doses in presence of inflammatory stimulus (Jacob et al, 2013 ; Galvão et al, 2017 ).…”
Section: Ouabain As a Modulator Of Inflammationcontrasting
confidence: 75%
See 1 more Smart Citation
“…It is noteworthy that in this study the authors used high doses of ouabain both in vitro and in vivo . This contrasts with other studies that show a reduction of a different pattern of cytokines, including IL-1β (Leite et al, 2015 ) with lower ouabain doses in presence of inflammatory stimulus (Jacob et al, 2013 ; Galvão et al, 2017 ).…”
Section: Ouabain As a Modulator Of Inflammationcontrasting
confidence: 75%
“…This ouabain effect was also demonstrated in peritoneal inflammation induced by mitogen concanavalin A (de Vasconcelos et al, 2011 ). Furthermore, in airway allergic inflammation model, ouabain has an anti-migratory effect (Galvão et al, 2017 ). Ray and Samanta ( 1997 ) have also demonstrated that ouabain impairs in vitro human neutrophil migration, by interfering with IL-8 receptor recycling.…”
Section: Ouabain As a Modulator Of Inflammationmentioning
confidence: 99%
“…Related researches also proposed ouabain reduced the polymorphonuclear leukocytes in animal models of peritonitis induced by concanavalin A and Leishmania amazonensis [ 9 , 10 ]. Ouabain was also proven to alleviate allergic airway inflammation in a mouse model, which inhibits inflammatory cell migration into the lungs [ 11 ]. Leite and colleagues demonstrated that ouabain reduced neutrophil migration and decreased vascular permeability in peritonitis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrated the anti-inflammatory and analgesic effects of ouabain by inhibiting NF-κB activation [ 9 , 10 ]. It has also been demonstrated that ouabain could negatively modulate airway inflammation in ovalbumin-induced asthma [ 11 ]. However, whether ouabain could regulate inflammatory responses in LPS-induced ALI in mice has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this steroid inhibits proinflammatory cytokines, such as interleukin 1 β (IL-1 β ) and tumor necrosis factor α (TNF- α ), which could be associated with p38 mitogen-activated protein kinase (MAPK p38) and nuclear factor kappa B- (NF- κ B-) reduced activity [22, 23]. Recently, another study of our group has shown that ouabain negatively modulates pulmonary inflammation, reducing eosinophil migration, Th2 profile cytokines, and mucus production in bronchioles [24]. Furthermore, by similar mechanisms, other studies demonstrated the anti-inflammatory effects of digoxin and bufalin [11, 12].…”
Section: Introductionmentioning
confidence: 99%